Kebutuhan Spiritual pada Pasien dengan Kanker Stadium Akhir - Maria Komariah; Dessy Adriani; Desy Indrayani; Nina Gartika (Jurnal Keperawatan Silampari, 2020)
This research aims to examine spiritual needs by getting an idea of the level of importance of spiritual needs based on the seven dimensions developed by Galek. This research method uses descriptive research methods. The results of research on the aspects of divinity (3.63), morality and ethics (3.43), love/sense of belonging (3.42), positive thinking/gratitude/hope (3.40), meaning and purpose (3.39) ), resolution/death (3.26) and on the appreciation dimension of beauty (2.98). In conclusion, in advanced cancer patients, the highest spiritual need is in the divine aspect, and the lowest is in the dimension of appreciation of beauty. Keywords: Study, Advanced Stage Cancer, Needs, Patients, Spiritual